ANALISIS PENGARUH PEMBERDAYAAN, MOTIVASI KERJA DAN BUDAYA ORGANISASIONAL TERHADAP KINERJA PEGAWAI (Studi Pada DPPKAD Kabupaten Grobogan) - Harry Hendra Prabowo, 0835020034 (Students Journal of Economic and Management, 2015)
This observation is an observation that research empowerment effect, work motivation, and organizational culture for servants performance. The purpose of this observation is DPPKAD grobogan regency servants: increasing empowerment affect for servants performance. The subject of this observation is DPPKAD grobogan regency servants that consist of 82 persons. Method of data collecting is population method and sample. It can be looked from : based the gender can be known that the respondents who dominate this observation is the men. They are 53 persons(67,1%) and the women are 26 persons(32,9%). Based of the age can be known that the respondents dominate 31-40 years old. They are 29 persons(36,7%). The second respondents are 41-50 years old. They are 25 persons(31,6%) and the third respondents are more than 50 years old. They are 13 persons(16,5%) and the servants are less than 31 years old, they are 12 persons (15,2%). From this observation can be concluded that empowerment, work motivation, organizational culture give effect for servants performance, especially for DPPKAD grobogan regency Key Word : Empowerment, Work Motivation, Organizational Culture